Strategic Analysis for Developing Tourism in Toba Regency: A Sustainable Management Approach - Muhammad Arif Lubis; Ayu Dhisa Faradiba Siregar (Journal Of Management Analytical and Solution (JoMAS), 2024)
Toba Regency, located in North Sumatra, Indonesia, offers vast potential for tourism development, thanks to its natural beauty, cultural heritage, and historical significance. This study analyzes the strengths, weaknesses, opportunities, and threats (SWOT) related to tourism in Toba Regency, utilizing a sustainable management approach to enhance the region's tourism sector. By conducting a SWOT analysis and evaluating both internal and external factors, the study identifies key strategies for boosting tourism, including improving infrastructure, increasing local community involvement, and promoting the region’s unique cultural and natural attractions at national and international levels. The findings suggest that leveraging Toba Regency's natural and cultural resources, while addressing limitations in infrastructure and community engagement, can significantly enhance its tourism potential. The strategic recommendations provided focus on sustainable practices that will benefit the local economy, preserve cultural and environmental assets, and foster long-term tourism growth.